Improvement of Bioactive Potential of Canavalia Beans of Coastal Sand Dunes by Solid-Substrate Fermentation Using Rhizopus oligosporus - R. Niveditha, Vedavyas; R. Sridhar, Kandikere; Tomita-Yokotani, Kaori (Current Nutrition & Food Science, 2014)
Cooked beans of two wild legumes (Canavalia cathartica and C. maritima) were subjected to solid-substrate fermentation by Rhizopus oligosporus and bioactive potential has been compared with raw and cooked beans. Flavonoids and canavanine in raw beans were significantly decreased on cooking, while they were significantly enhanced in fermented beans. Phytic acid content was signficantlty decreased from raw vs. cooked vs. fermented beans. Raw, cooked and fermented beans were devoid of trypsin inhibitors. Hemagglutinin activity of raw beans was completely eliminated on cooking, while SSF increased its activity about 50% of raw beans against A+ve and or B+ve blood groups. Solid-substrate fermentation of cooked beans with R. oligosporus resulted in better nutraceutical potential compared to raw and mearly cooked beans qualifying as important nutraceutical source to develop indigenous value-added products.
Keywords: coastal sand dunes